2016
DOI: 10.21475/ajcs.2016.10.06.p7520
|View full text |Cite
|
Sign up to set email alerts
|

The first high-density sequence characterized SNP-based linkage map of olive (Olea europaea L. subsp. europaea) developed using genotyping by sequencing

Abstract: A number of linkage maps have been previously developed in olive; however, these are mostly composed of markers that have not been characterized at the sequence level, supplemented with smaller numbers of microsatellite markers. In this investigation, we sought to develop a saturated linkage mapping resource for olive composed entirely of sequence characterized markers. We employed genotyping by sequencing to develop a map of a F 2 population derived from the selfing of the cultivar Koroneiki. The linkage map … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…They are in agreement with conclusions of studies that tested SI in O. europaea at the postzygotic level, by measuring seed production after controlled crosses or open pollination, together with paternity analysis of the progeny (De la Rosa et al., ; Díaz et al., ; Marchese, Marra, Caruso, et al. ; Marchese, Marra, Costa, et al., ; Mookerjee et al., ). Just as in our study, many studies observed seeds produced by selfing either from controlled crosses with pollen from incompatible genotypes (see Oit28, Oit55, and Oit57 in Tables S3 and S4) or in controlled selfing (Farinelli et al., ) or open pollination (Marchese, Marra, Costa, et al., ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…They are in agreement with conclusions of studies that tested SI in O. europaea at the postzygotic level, by measuring seed production after controlled crosses or open pollination, together with paternity analysis of the progeny (De la Rosa et al., ; Díaz et al., ; Marchese, Marra, Caruso, et al. ; Marchese, Marra, Costa, et al., ; Mookerjee et al., ). Just as in our study, many studies observed seeds produced by selfing either from controlled crosses with pollen from incompatible genotypes (see Oit28, Oit55, and Oit57 in Tables S3 and S4) or in controlled selfing (Farinelli et al., ) or open pollination (Marchese, Marra, Costa, et al., ).…”
Section: Discussionsupporting
confidence: 88%
“…The leaky SI observed in olive has provided material for genetic mapping and sequencing (Marchese, Marra, Caruso, et al. ) and allows an opportunity to measure inbreeding depression. For example, in the wild relative P. angustifolia , 2% of 2,000 surveyed seedlings produced from controlled crosses were found to have been selfed (Billiard et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…These data were further considered to construct a set of core collections of the olive accessions maintained in the germplasm. The SNPs were further used for: (1) the analysis of genetic identity among five putative clones of the olive cultivar Souri (Ben-Ari et al 2014); (2) the traceability of olive oil (Kalogianni et al 2015) also by developing peptide nucleic acid (PNA) and modified-PNA microarrays (Rossi et al 2012); (3) genetic mapping (Marchese et al 2016a;Ipek et al 2016;.…”
Section: Snpsmentioning
confidence: 99%
“…Ipek et al (2016) and Marchese et al (2016a) used GBS (Genotyping by Sequencing) to generate a high number of SNPs to obtain highly saturated genetic maps with a higher resolution capacity than those of the existing genetic maps. Ipek et al (2016) identified 10,941 new SNPs by applying GBS.…”
Section: Genetic Mappingmentioning
confidence: 99%
See 1 more Smart Citation